A gel system for blocking CO2 gas channeling in low permeability oil reservoirs, a preparation method and applications thereof
Patent Information
- Application Number
- CN202610977330.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-02
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-07-02
AI Technical Summary
但现有凝胶体系在低渗油藏CO2气窜封堵应用中,仍存在诸多技术缺陷,无法满足现场实际需求
1.根据本申请的用于低渗油藏封堵CO2气窜的凝胶体系,采用AM-AMPS二元共聚物配合复合交联剂,该体系在近井中性弱碱环境中保持低黏度、流动性优异,可顺利注入低渗储层微小孔喉;仅在地层CO2溶解形成酸性环境后缓慢活化交联,实现深部原位可控成胶;聚合物分子链携带磺酸基团,具备优异耐酸耐盐能力,凝胶骨架结构稳定,从根源上提升低渗油藏深部气窜通道的封堵针对性与适配性。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This application relates to a gel system for plugging CO2 gas channeling in low-permeability reservoirs, its preparation method, and its application, belonging to the technical field of oilfield gas channeling plugging agents. Background Technology
[0002] Low-permeability reservoirs are an important replacement resource for oil and gas exploration and development in my country. Their geological reserves account for the majority of the country's newly added oil and gas reserves. However, these reservoirs generally have characteristics such as poor pore connectivity, low permeability, and high fluid flow resistance. Under conventional development methods, the crude oil recovery rate is extremely low, and the development is extremely difficult.
[0003] CO2 flooding technology, due to CO2's excellent permeability, can penetrate into tiny pores that are difficult for water to reach. It effectively improves oil recovery in low-permeability reservoirs while also achieving CO2 sequestration, aligning with carbon emission reduction goals, making it a core technology for the efficient development of such reservoirs. However, during CO2 flooding development in low-permeability reservoirs, CO2 easily channels along high-permeability channels due to differences in oil and gas viscosity and reservoir heterogeneity. This significantly reduces CO2 sweep efficiency, not only hindering oil recovery but also wasting CO2, increasing development costs, and even posing environmental safety hazards. Therefore, CO2 channeling prevention has become a critical technical challenge that urgently needs to be addressed in the CO2 flooding development of low-permeability reservoirs.
[0004] Currently, gel systems have become one of the mainstream technologies for CO2 gas channeling plugging in low-permeability reservoirs due to their excellent plugging performance. Existing gel plugging systems mostly use polymers as the matrix and combine them with crosslinking agents to form a three-dimensional network structure to block CO2 gas channeling. However, existing gel systems still have many technical defects in the application of CO2 gas channeling plugging in low-permeability reservoirs and cannot meet the actual needs of the field. On the one hand, existing gel systems mostly use conventional thermal crosslinking or single retarded crosslinking systems. Either the crosslinking rate is too fast, causing the gel to gel prematurely and accumulate near the wellbore, preventing it from penetrating deep into low-permeability reservoirs and hindering the sealing of deep gas channeling; or the crosslinking rate is too slow, failing to effectively gel at depth, resulting in poor sealing performance. Furthermore, some crosslinking systems use phenolic, formaldehyde, or urea-based retarders, posing environmental risks and exhibiting poor acid resistance, easily degrading and failing under long-term acidic conditions. On the other hand, the gel matrix lacks sufficient acid and salt resistance. In low-permeability reservoirs with high salinity and strong acidity, polymer molecular chains are prone to hydrolysis and breakage, causing damage to the gel skeleton, reduced sealing strength, and inability to withstand long-term CO2 erosion. Simultaneously, to achieve delayed gelation, the crosslinking density needs to be reduced, further resulting in lower overall gel strength, making it prone to erosion, breakage, and collapse, hindering long-term sealing.
[0005] In existing technologies, reinforcing fillers such as silica, bentonite, and alumina are often introduced to enhance the mechanical strength and shear resistance of gels. However, conventional reinforcing fillers usually suffer from problems such as easy agglomeration and poor acid resistance. Therefore, some studies have used modified fillers to improve performance. For example, Chinese patent CN 121759180 A describes a polymeric pre-crosslinked gel particle plugging agent suitable for carbon dioxide flooding reservoirs and its preparation method. It uses polymerizable modified silica with double bonds on its surface as an inorganic reinforcing agent to improve the mechanical strength of the gel. However, this modification method only introduces polymerizable double bonds, which can only participate in polymerization to achieve simple reinforcement. It is not suitable for the acidic environment of supercritical CO2 reservoirs, nor can it form a synergistic effect with the various components of the gel, making it difficult to meet the needs of deep plugging and long-term stabilization in low-permeability reservoirs.
[0006] Therefore, developing a gel system that is suitable for CO2 flooding in low-permeability reservoirs, is acid and salt resistant, has long-term stability, and has excellent synergistic plugging effect has become an urgent need in the field of CO2 gas channeling plugging in low-permeability reservoirs. Summary of the Invention
[0007] To address the aforementioned issues, this application provides a gel system, its preparation method, and its application for sealing CO2 gas channeling in low-permeability reservoirs. This application specifies the composition and proportions of each component in the gel system. Deep delayed gelation is achieved through the combined action of AM-AMPS copolymer and a composite crosslinking agent, solving the problem of premature near-wellbore sealing. The pre-crosslinked nanospheres are deformable and can pass through low-permeability pore throats, providing both acid resistance and reinforcement. Combined with stabilizers and reinforcing fillers, the gel strength is enhanced, preventing microsphere aggregation and phase separation. The system is acid and salt resistant, long-lasting, and stable. The preparation process is simple and can be implemented in-situ, effectively sealing CO2 gas channeling and synergistically improving oil recovery and CO2 sequestration efficiency.
[0008] According to one aspect of this application, a gel system for plugging CO2 gas channeling in low-permeability reservoirs is provided, comprising, by mass fraction, 7-11% AM-AMPS binary copolymer, 2-4.5% composite crosslinking agent, 2-5% nano-pre-crosslinked microspheres, 1-2% stabilizer, 0.5-1.5% reinforcing filler, and the balance being water.
[0009] Specifically, the AM-AMPS binary copolymer is a copolymer of acrylamide (AM) and 2-acrylamido-2-methylpropanesulfonic acid (AMPS), and the relative molecular weight of the AM-AMPS binary copolymer is 15-20 million. The AM-AMPS binary copolymer is prepared by the following method: using acrylamide monomer and 2-acrylamido-2-methylpropanesulfonic acid monomer as copolymer raw materials, the mass ratio of acrylamide monomer to 2-acrylamido-2-methylpropanesulfonic acid monomer is 7:3, and deionized water is used as the reaction solvent to prepare the total monomer content. A 20%–30% aqueous solution was prepared; the pH of the system was adjusted to 6.0–7.0 using sodium bicarbonate, and dissolved oxygen was removed by continuously purging high-purity nitrogen gas for 30 minutes; a redox initiation system of ammonium persulfate and sodium bisulfite in a mass ratio of 4:1 was selected, and the total amount of initiator added was 0.2%–0.3% of the total mass of monomers; the polymerization was carried out in a closed system at a constant temperature of 20–30℃ for 3–5 hours, and a transparent gel block was obtained after polymerization; the gel block was dried, crushed, and sieved to obtain a white powdered random copolymer of acrylamide and 2-acrylamido-2-methylpropanesulfonic acid.
[0010] Specifically, this application defines the components, proportions, and mass fractions of the gel system. The AM-AMPS copolymer serves as the basic framework, and its molecular chain contains a large number of highly polar sulfonic acid groups. It is resistant to salt and strong acid and can adapt to acidic environments. The AM-AMPS copolymer and the composite crosslinking agent work together to solve the core problems of premature near-wellbore sealing, difficulty in gelling at depth, and inability to reach gas channeling channels.
[0011] Optionally, the composite crosslinking agent includes zirconium salt, itaconic acid and sorbitol, with a mass ratio of (0.3~0.5):1:(1.2~1.8).
[0012] Specifically, this application specifies the composition and proportion of the composite crosslinking agent. In a weakly alkaline or neutral environment near the well, itaconic acid completely ionizes into carboxylate ions, and a large number of ortho-hydroxyl groups of sorbitol are in a hydrogen-bonded state; the carboxylate ions and ortho-hydroxyl groups synergistically chelate Zr. 4+ It forms a chelate complex, which locks in zirconium and passivates cross-linking activity. It does not gel or cross-link, and can be injected at low viscosity without pre-sealing near the well. In an acidic environment, the chelate structure dissociates protons, gradually releasing zirconium ions to coordinate and cross-link with AM-AMPS polymers. At the same time, itaconic acid and sorbitol assist in cross-linking and provide synchronous reinforcement.
[0013] Specifically, zirconium salts include zirconium oxychloride.
[0014] Optionally, the nano-precrosslinked microspheres are acrylamide-acrylic acid-glycidyl methacrylate terpolymer precrosslinked flexible microspheres, the stabilizer is dodecyl dimethyl betaine, and the reinforcing filler is modified hydrophobic nano silica.
[0015] Specifically, glycidyl methacrylate with epoxy active groups is introduced and combined with acrylamide and acrylic acid to form a ternary slightly pre-crosslinked network, which fills the gaps in the gel network and strengthens the gel strength; it is highly flexible and compressible, and can be squeezed into the nano- and micro-scale pores and throats of low-permeability reservoirs; the molecular structure is stable and resistant to acidic environments without hydrolysis or breakage; at the same time, the surface epoxy groups can form an interface with modified silica and polymer chains to resist CO2 erosion and loss, and make up for the defects of low crosslinking density and insufficient strength of delayed crosslinked gels.
[0016] Optionally, the preparation method of the acrylamide-acrylic acid-glycidyl methacrylate terpolymer pre-crosslinked flexible microspheres includes the following steps: S1. Acrylamide, acrylic acid, glycidyl methacrylate, crosslinking agent, and emulsifier are added to deionized water and stirred until completely dissolved. The pH of the system is adjusted to 7.0~7.5. The mixture is then emulsified for 30~40 min at 30~40℃ and 300~500 r / min to form a uniform emulsion. S2 is added as an initiator, and the reaction is carried out at a constant temperature of 40~50℃ for 2~3 hours to achieve in-situ polymerization and pre-crosslinking; After the S3 reaction is completed, the mixture is centrifuged, washed 2-3 times with deionized water, air-dried at room temperature, and pulverized to obtain acrylamide-acrylic acid-glycidyl methacrylate terpolymer pre-crosslinked flexible microspheres.
[0017] Specifically, monomers form tiny droplets under the action of emulsifiers, initiators initiate polymerization, crosslinking agents achieve mild pre-crosslinking inside the particles, and post-treatment yields dried microspheres to obtain acrylamide-acrylic acid-glycidyl methacrylate terpolymer pre-crosslinked flexible microspheres with uniform particle size, good flexibility, acid resistance, and epoxy groups on the surface.
[0018] Optionally, the mass ratio of acrylamide, acrylic acid, and glycidyl methacrylate is (7~8):2:1; the amount of the initiator is 0.2~0.4% of the total mass of the acrylamide, acrylic acid, and glycidyl methacrylate; the initiator includes ammonium persulfate and sodium bisulfite, with a mass ratio of (2.5~3.5):1; the crosslinking agent is N,N'-methylenebisacrylamide, and the amount of the crosslinking agent is 0.5~1% of the total mass of the monomers; the emulsifier is sodium dodecyl sulfate, and the amount of the emulsifier is 0.3~0.6% of the total mass of the monomers.
[0019] Specifically, this application specifies the requirements for each raw material and its dosage. This application specifies the mass ratio of acrylamide, acrylic acid, and glycidyl methacrylate to achieve a balance between acid resistance, flexibility, and epoxy activity. The initiator ensures the crosslinking strength, and the emulsifier controls the particle size to obtain microspheres with slight crosslinking, good dispersibility, and no agglomeration.
[0020] Optionally, the modified hydrophobic nano-silica is prepared by the following steps: S01 mixes nano-silica, ethanol, and water, stirs and ultrasonically disperses them to form a nano-silica dispersion; SO2 is added to a nano-silica dispersion as a silane coupling agent, and the mixture is refluxed at 55-65°C for 2-3 hours. Then, stearic acid is added, and the reaction continues for another 1.5-2 hours. After the SO3 reaction is completed, the modified hydrophobic nano-silica is obtained by centrifugation, washing, drying, grinding and sieving.
[0021] Specifically, nano-silica is grafted with epoxy groups by KH-560 and then with hydrophobic long chains by stearic acid to achieve dual-function modification, which greatly improves its acid resistance and high mineralization resistance, and avoids the hydrophilic aggregation and degradation failure of inorganic fillers in acidic environments. On the other hand, the epoxy sites on its surface can be bonded and anchored with nano-pre-crosslinked microspheres and AM-AMPS binary copolymers, changing from simple physical filling to interfacial chemical reinforcement, filling gel network defects, improving mechanical strength and shear resistance.
[0022] Optionally, the mass ratio of the nano-silica, ethanol, and water is (1~1.2):(8~8.5):(1.5~2); the silane coupling agent is KH-560, and the amount of the silane coupling agent is 4~6% of the mass of the nano-silica; the amount of stearic acid is 3~4% of the mass of the nano-silica.
[0023] Specifically, this application limits the dosage of each ingredient to ensure sufficient modification, no agglomeration, no residue, uniform modification, stable surface activity, strong acid resistance, and excellent dispersibility.
[0024] According to another aspect of this application, a method for preparing the above-mentioned gel system for plugging CO2 gas channeling in low-permeability reservoirs is also provided, comprising the following steps: (1) Add metered oilfield reinjection water and stabilizer to the liquid preparation tank and stir thoroughly until completely dissolved; (2) Add reinforcing filler and stir continuously to form a stable inorganic dispersion; (3) Slowly add the AM-AMPS binary copolymer and stir to allow the polymer to fully swell and dissolve; (4) Add the composite crosslinking agent and stir for 30-40 min to obtain a low-viscosity pregel solution; (5) Add nano pre-crosslinked microspheres, stir evenly, let stand to defoam, and obtain a gel system for blocking CO2 gas channeling in low-permeability reservoirs.
[0025] Specifically, this application defines the steps of the preparation method of the gel system for blocking CO2 gas channeling in low-permeability reservoirs, and specifically defines the order of adding each raw material. First, the reinforcing filler is dispersed to avoid uneven encapsulation of the polymer in the later stage. The crosslinking agent is added last to ensure delayed gelation, so as to achieve a system with low viscosity, no agglomeration, no stratification, and direct injection.
[0026] Optionally, in step (1), the stirring speed is 300~500 r / min; in step (3), the stirring speed is 400~600 r / min; in step (5), the stirring speed is 200~300 r / min; in step (4), the pH of the low viscosity pregel solution system is maintained at 7.5~8.8.
[0027] Specifically, this application limits the process parameters in the preparation process, controls the rotation speed to protect the microsphere structure and ensure that the polymer swells fully; and limits the pH to control the timing of crosslinking, so that the near-wellbore area is in an inert dormant state, and after entering the deep formation and encountering supercritical CO2 to form an acidic environment, it is gradually activated and slowly condenses and crosslinks into a gel.
[0028] According to another aspect of this application, the application of the above-mentioned gel system for plugging CO2 gas channeling in low-permeability reservoirs is also provided.
[0029] The beneficial effects of this application include, but are not limited to: 1. The gel system for plugging CO2 gas channeling in low-permeability reservoirs according to this application uses an AM-AMPS binary copolymer combined with a composite crosslinking agent. This system maintains low viscosity and excellent fluidity in a near-wellbore neutral weak alkaline environment, and can be smoothly injected into the micropore throats of low-permeability reservoirs. It only slowly activates crosslinking after the formation CO2 dissolves to form an acidic environment, realizing controllable in-situ gelation in deep reservoirs. The polymer molecular chains carry sulfonic acid groups, which have excellent acid and salt resistance. The gel skeleton structure is stable, which fundamentally improves the targeting and adaptability of plugging deep gas channeling channels in low-permeability reservoirs.
[0030] 2. The gel system for plugging CO2 gas channeling in low-permeability reservoirs according to this application introduces acrylamide-acrylic acid-glycidyl methacrylate ternary copolymer flexible microspheres. The microspheres are flexible and deformable, and can adapt to the micropore throats of low-permeability reservoirs to complete deep retention. The overall erosion resistance of the gel is enhanced through physical filling and skeleton support. At the same time, it has excellent acid resistance and mineralization resistance, and can exist stably in complex formation environments of CO2 flooding for a long time, avoiding gel breakage and loss, and significantly extending the effective period of plugging.
[0031] 3. The preparation method of the gel system for blocking CO2 gas channeling in low-permeability reservoirs according to this application has readily available raw materials, a simple and mild preparation process, and an overall preparation process that is suitable for large-scale liquid preparation construction in oilfields. It does not require complex equipment with high temperature and high pressure, has low construction cost, strong operability, and is easy to promote and apply. Detailed Implementation
[0032] The present application is described in detail below with reference to the embodiments, but the present application is not limited to these embodiments.
[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of skill in the art. The reagents and raw materials used in this invention are readily available through conventional means, and unless otherwise specified, they shall be used in accordance with conventional methods in the art or as per the product instructions. Furthermore, any methods and materials similar to or equivalent to those described herein may be applied to the methods of this invention. The preferred embodiments and materials described in this patent are for illustrative purposes only.
[0034] In the following examples and comparative examples, the AM-AMPS binary copolymers were prepared by the following method: Acrylamide monomer and 2-acrylamido-2-methylpropanesulfonic acid monomer were used as copolymer raw materials, with a mass ratio of acrylamide monomer to 2-acrylamido-2-methylpropanesulfonic acid monomer of 7:3. Deionized water was used as the reaction solvent to prepare an aqueous solution with a total monomer mass fraction of 25%. The pH of the system was adjusted to 6.5 using sodium bicarbonate, and high-purity nitrogen was continuously purged for 30 minutes to remove dissolved oxygen. An ammonium persulfate-sodium bisulfite redox initiation system was selected with a mass ratio of 4:1, and the total amount of initiator added was 0.25% of the total monomer mass. The polymerization was carried out at a constant temperature of 25℃ in a closed system for 4 hours. After polymerization, a transparent gel block was obtained. The gel block was dried, crushed, and sieved to obtain a white powdered random copolymer of acrylamide and 2-acrylamido-2-methylpropanesulfonic acid.
[0035] Example 1: Preparation of a gel system for plugging CO2 gas channeling in low-permeability reservoirs The raw material composition, by mass fraction, includes: 7% AM-AMPS binary copolymer, 2% composite crosslinking agent (zirconium oxychloride: itaconic acid: sorbitol = 0.3:1:1.2), 2% nano-pre-crosslinked microspheres, 1% stabilizer dodecyl dimethyl betaine, 0.5% reinforcing filler, and the balance being water; the specific preparation steps are as follows: (1) Add metered oilfield reinjection water and stabilizer to the liquid preparation tank, stir thoroughly until completely dissolved, and rotate at 300 r / min; (2) Add reinforcing filler and stir continuously to form a stable inorganic dispersion; (3) Slowly add the AM-AMPS binary copolymer and stir to allow the polymer to fully swell and dissolve. The stirring speed is 400 r / min. (4) Add the composite crosslinking agent and stir for 30 min to obtain a low viscosity pregel solution. The pH of the low viscosity pregel solution system is naturally maintained at 7.5. (5) Add nano pre-crosslinked microspheres, stir evenly at a stirring speed of 200 r / min, let stand to defoam, and obtain a gel system for blocking CO2 gas channeling in low-permeability reservoirs.
[0036] Preparation of pre-crosslinked nanospheres: S1. Acrylamide, acrylic acid, glycidyl methacrylate, crosslinking agent N,N'-methylenebisacrylamide, and emulsifier sodium dodecyl sulfate are added to deionized water. The mass ratio of acrylamide, acrylic acid, and glycidyl methacrylate is 7:2:1. The amount of crosslinking agent is 0.5% of the total mass of monomers, and the amount of emulsifier is 0.3% of the total mass of monomers. The mixture is stirred until completely dissolved, and the pH of the system is adjusted to 7.0. The mixture is then emulsified for 30 minutes at 30°C and 300 r / min to form a homogeneous emulsion. S2 is added with an initiator (ammonium persulfate: sodium bisulfite = 2.5:1), and the amount of initiator is 0.2% of the total mass of acrylamide, acrylic acid, and glycidyl methacrylate. The reaction is carried out at a constant temperature of 40℃ for 2 hours to achieve in-situ polymerization and pre-crosslinking. After the S3 reaction was completed, the mixture was centrifuged, washed twice with deionized water, air-dried at room temperature, and pulverized to obtain acrylamide-acrylic acid-glycidyl methacrylate terpolymer pre-crosslinked flexible microspheres.
[0037] Preparation of reinforcing fillers: S01 mixes nano-silica, ethanol, and water in a mass ratio of 1:8:1.5, stirs, and ultrasonically disperses the mixture to form a nano-silica dispersion. S02 added silane coupling agent KH-560 to the nano silica dispersion. The amount of silane coupling agent was 4% of the mass of nano silica. After refluxing at 55°C for 2 hours, stearic acid was added. The amount of stearic acid was 3% of the mass of nano silica. The reaction continued for 1.5 hours. After the SO3 reaction is completed, the modified hydrophobic nano-silica is obtained by centrifugation, washing, drying, grinding and sieving.
[0038] Example 2: Preparation of a gel system for plugging CO2 gas channeling in low-permeability reservoirs: The raw material composition, by mass fraction, includes: 11% AM-AMPS binary copolymer, 4.5% composite crosslinking agent (zirconium oxychloride: itaconic acid: sorbitol = 0.5:1:1.8), 5% nano-pre-crosslinked microspheres, 2% stabilizer dodecyl dimethyl betaine, 1.5% reinforcing filler, and the balance being water; the specific preparation steps are as follows: (1) Add metered oilfield reinjection water and stabilizer to the liquid preparation tank, stir thoroughly until completely dissolved, and rotate at 500 r / min; (2) Add reinforcing filler and stir continuously to form a stable inorganic dispersion; (3) Slowly add the AM-AMPS binary copolymer and stir to allow the polymer to fully swell and dissolve. The stirring speed is 600 r / min. (4) Add the composite crosslinking agent and stir for 40 min to obtain a low-viscosity pregel solution. The pH of the low-viscosity pregel solution system is naturally maintained at 7.5. (5) Add nano pre-crosslinked microspheres, stir evenly at a stirring speed of 300 r / min, let stand to defoam, and obtain a gel system for blocking CO2 gas channeling in low-permeability reservoirs.
[0039] Preparation of pre-crosslinked nanospheres: S1. Acrylamide, acrylic acid, glycidyl methacrylate, crosslinking agent N,N'-methylenebisacrylamide, and emulsifier sodium dodecyl sulfate are added to deionized water. The mass ratio of acrylamide, acrylic acid, and glycidyl methacrylate is 8:2:1. The amount of crosslinking agent is 1% of the total mass of monomers, and the amount of emulsifier is 0.6% of the total mass of monomers. The mixture is stirred until completely dissolved, and the pH of the system is adjusted to 7.0. The mixture is then emulsified for 40 minutes at 40°C and 500 r / min to form a homogeneous emulsion. S2 is added with an initiator (ammonium persulfate: sodium bisulfite = 3.5: 1). The amount of initiator is 0.4% of the total mass of acrylamide, acrylic acid, and glycidyl methacrylate. The reaction is carried out at a constant temperature of 50°C for 3 hours to achieve in-situ polymerization and pre-crosslinking. After the S3 reaction was completed, the mixture was centrifuged, washed three times with deionized water, air-dried at room temperature, and pulverized to obtain acrylamide-acrylic acid-glycidyl methacrylate terpolymer pre-crosslinked flexible microspheres.
[0040] Preparation of reinforcing fillers: S01 mixes nano-silica, ethanol, and water in a mass ratio of 1.2:8.5:2, stirs, and ultrasonically disperses the mixture to form a nano-silica dispersion. S02 added silane coupling agent KH-560 to the nano-silica dispersion, the amount of silane coupling agent being 6% of the mass of nano-silica. After refluxing at 65°C for 3 hours, stearic acid was added, the amount of stearic acid being 4% of the mass of nano-silica, and the reaction was continued for 2 hours. After the SO3 reaction is completed, the modified hydrophobic nano-silica is obtained by centrifugation, washing, drying, grinding and sieving.
[0041] Example 3: Preparation of a gel system for plugging CO2 gas channeling in low-permeability reservoirs: The raw material composition, by mass fraction, includes: 9% AM-AMPS binary copolymer, 3% composite crosslinking agent (zirconium oxychloride: itaconic acid: sorbitol = 0.4:1:1.5), 3% nano-pre-crosslinked microspheres, 1.5% stabilizer dodecyl dimethyl betaine, 0.8% reinforcing filler, and the balance being water; the specific preparation steps are as follows: (1) Add metered oilfield reinjection water and stabilizer to the mixing tank, stir thoroughly until completely dissolved, and rotate at 400 r / min; (2) Add reinforcing filler and stir continuously to form a stable inorganic dispersion; (3) Slowly add the AM-AMPS binary copolymer and stir to allow the polymer to fully swell and dissolve. The stirring speed is 500 r / min. (4) Add the composite crosslinking agent and stir for 35 min to obtain a low-viscosity pregel solution. The pH of the low-viscosity pregel solution system is naturally maintained at 7.5. (5) Add nano pre-crosslinked microspheres, stir evenly at a stirring speed of 250 r / min, let stand to defoam, and obtain a gel system for blocking CO2 gas channeling in low-permeability reservoirs.
[0042] Preparation of pre-crosslinked nanospheres: S1. Acrylamide, acrylic acid, glycidyl methacrylate, crosslinking agent N,N'-methylenebisacrylamide, and emulsifier sodium dodecyl sulfate are added to deionized water. The mass ratio of acrylamide, acrylic acid, and glycidyl methacrylate is 7.5:2:1. The amount of crosslinking agent is 0.8% of the total mass of monomers, and the amount of emulsifier is 0.5% of the total mass of monomers. The mixture is stirred until completely dissolved, and the pH of the system is adjusted to 7.0. The mixture is then emulsified for 35 minutes at 35°C and a stirring speed of 400 r / min to form a uniform emulsion. S2 is added with an initiator (ammonium persulfate: sodium bisulfite = 3:1), and the amount of initiator is 0.3% of the total mass of acrylamide, acrylic acid, and glycidyl methacrylate. The reaction is carried out at a constant temperature of 45℃ for 2.5 hours to achieve in-situ polymerization and pre-crosslinking. After the S3 reaction was completed, the mixture was centrifuged, washed three times with deionized water, air-dried at room temperature, and pulverized to obtain acrylamide-acrylic acid-glycidyl methacrylate terpolymer pre-crosslinked flexible microspheres.
[0043] Preparation of reinforcing fillers: S01 mixes nano-silica, ethanol, and water in a mass ratio of 1.2:8.5:1.5, stirs, and ultrasonically disperses the mixture to form a nano-silica dispersion. S02 added silane coupling agent KH-560 to the nano silica dispersion. The amount of silane coupling agent was 5% of the mass of nano silica. After refluxing at 60°C for 2.5 h, stearic acid was added. The amount of stearic acid was 3.5% of the mass of nano silica. The reaction continued for 2 h. After the SO3 reaction is completed, the modified hydrophobic nano-silica is obtained by centrifugation, washing, drying, grinding and sieving.
[0044] Example 4 The difference between Example 4 and Example 3 is that in the preparation of the nano-pre-crosslinked microspheres, the mass ratio of acrylamide, acrylic acid, and glycidyl methacrylate is 1:1:1, while the rest are the same.
[0045] Example 5 The difference between Example 5 and Example 3 is that the preparation of the reinforcing filler does not include the step of adding stearic acid, but the rest are the same.
[0046] Example 6 The difference between Example 6 and Example 3 is that the reinforcing filler is unmodified nano-silica, while the rest are the same.
[0047] Comparative Example 1 The difference between Comparative Example 1 and Example 3 is that the latter does not include the composite crosslinking agent, while all other aspects are the same.
[0048] Comparative Example 2 The difference between Comparative Example 2 and Example 3 is that Comparative Example 2 does not include nano-pre-crosslinked microspheres, but all other aspects are the same.
[0049] Comparative Example 3 The difference between Comparative Example 3 and Example 3 is that the composite crosslinking agent contains only zirconium oxychloride, while the rest are the same.
[0050] Comparative Example 4 The difference between Comparative Example 4 and Example 3 is that the composite crosslinking agent does not include itaconic acid, but all other aspects are the same.
[0051] Comparative Example 5 The difference between Comparative Example 5 and Example 3 is that the composite crosslinking agent does not include sorbitol, but all other components are the same.
[0052] Experiment 1: Gel Formation Time Test In the examples and comparative examples, equal amounts of gel system solutions were placed in sample bottles, adjusted to the corresponding pH, and placed in a 60°C constant temperature oven. Every 30 minutes, the sample bottles were tilted and inverted to observe the fluidity of the system. The gelation time was recorded as the time when the system completely lost its fluidity and the bottle did not flow when inverted. The test results are shown in Table 1.
[0053] Table 1 Results of gelation time test
[0054] Table 1 shows that Examples 1-3 of the present invention all had gelation times >12h in a weakly alkaline environment (pH=7.5), indicating a dormant state that enabled low-viscosity injection and deep migration; in an acidic environment (pH=3.0), they achieved rapid gelation within 3-4h. Comparative Example 1 could not gel without a crosslinking agent; Comparative Example 3 only contained zirconium oxychloride, lacking itaconic acid and sorbitol chelating ligands, and could not passivate zirconium ion activity under weakly alkaline conditions, gelling prematurely in just 2.5h at pH=7.5; under acidic conditions, without ligand buffering, gelation was even faster, resulting in a loss of deep delayed profile control capability; Comparative Examples 4 and 5 lacked the synergistic effect of itaconic acid and sorbitol, posing a risk of premature near-wellbore crosslinking and plugging.
[0055] Experimental Example 2: Gel Strength Grade Test Using the Sydansk bottle test method, the fully gelled samples from the examples and comparative examples were stabilized at a constant temperature of 60°C for 2 hours, and the gel strength grade 1 was determined according to the industry-standard grading criteria (A~I). The fully gelled samples from the examples and comparative examples were placed in a simulated formation aqueous solution at pH 3.0 and placed in a constant temperature incubator at 60°C for 7 days. After removal, the gel strength grade 2 was measured. The test results are shown in Table 2.
[0056] Table 2 Results of gel strength grade test
[0057] Table 2 shows that the initial gel strength grades of Examples 1-3 were H-I. After aging in a strongly acidic environment (pH=3.0) for 7 days, they still maintained strength grades G-H, demonstrating outstanding acid resistance. Example 3 exhibited the best strength, reaching grade I initially and maintaining grade H after aging. Examples 4-7 showed a significant decrease in strength and acid resistance. Comparative Example 2 had a strength grade of only D, which dropped to grade C after aging. The reason for this was the lack of the pre-crosslinked nanospheres, which failed to meet the requirements for long-term sealing.
[0058] Experiment Example 3: Sand-filled pipe displacement experiment A sand-filled pipe displacement experiment was conducted. Low-permeability artificial quartz sand was used to fill the pipes to simulate the pore media of a low-permeability oil reservoir. The pipe specifications were Φ25 mm × 300 mm. Simulated oilfield formation water was used in the experiment, after filtration and degassing. The experimental temperature was set at the reservoir formation temperature of 60℃. Specific procedures are as follows: Low-permeability sand-filled pipes were prepared by compacting quartz sand of different mesh sizes. These pipes were connected to a displacement device and allowed to stand in a constant temperature of 60℃ with saturated formation water for 12 hours to allow the internal pore medium to reach a water-wet equilibrium. Formation water was then displaced forward at a constant displacement rate. After the pressure stabilized, the steady-state displacement pressure difference was recorded, and the initial aqueous permeability K1 of the sand-filled pipe was calculated using Darcy's law. A 0.2 PV gel system solution was injected forward into the sand-filled pipe at a constant injection rate. After injection, the valves at both ends of the sand-filled pipe were closed, and the pipe was placed in a sealed environment at 60℃ for 24 hours to allow for gel formation and ensure full cross-linking and solidification to form a sealing gel. After gel formation, formation water was continuously displaced forward at the same displacement rate, and the displacement pressure changes were recorded in real time. After the pressure reached a steady state again, the aqueous permeability K2 after sealing was calculated. The critical pressure at which fluid flow occurred in the sand-filled pipe was recorded as the gel sealing breakthrough pressure. Blocking rate (%) = [(K1-K2) / K1] × 100% Table 3. Test results of sand-filled pipe displacement experiment
[0059] Table 3 shows that Examples 1-3 all achieved a plugging rate higher than 89% and a breakthrough pressure higher than 6.2 MPa, demonstrating excellent plugging performance. Example 3 achieved a plugging rate of 93.5% and a breakthrough pressure of 7.8 MPa, exhibiting the best overall performance. Examples 4-7 showed significantly reduced plugging performance; Comparative Example 2, without nanosphere support, had a plugging rate of only 58.1%, making it difficult to effectively suppress CO2 gas migration.
[0060] The above description is merely an embodiment of this application, and the scope of protection of this application is not limited to these specific embodiments, but is determined by the claims of this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the technical concept and principles of this application should be included within the scope of protection of this application.
Claims
1. A gel system for plugging CO2 gas channeling in low-permeability reservoirs, characterized in that, The composition, by mass fraction, includes 7-11% AM-AMPS binary copolymer, 2-4.5% composite crosslinking agent, 2-5% nano-pre-crosslinked microspheres, 1-2% stabilizer, 0.5-1.5% reinforcing filler, and the balance being water; the nano-pre-crosslinked microspheres are acrylamide-acrylic acid-glycidyl methacrylate terpolymer pre-crosslinked flexible microspheres; the composite crosslinking agent includes zirconium salt, itaconic acid, and sorbitol, with a mass ratio of (0.3-0.5):1:(1.2-1.8); the reinforcing filler is modified hydrophobic nano-silica; and the stabilizer is dodecyl dimethyl betaine. The gel system used for blocking CO2 gas channeling in low-permeability reservoirs was prepared by the following method: (1) Add metered oilfield reinjection water and stabilizer to the liquid preparation tank and stir thoroughly until completely dissolved; (2) Add reinforcing filler and stir continuously to form a stable inorganic dispersion; (3) Slowly add the AM-AMPS binary copolymer and stir to allow the polymer to fully swell and dissolve; (4) Add the composite crosslinking agent and stir for 30 to 40 minutes to obtain a low-viscosity pregel solution; (5) Add nano pre-crosslinked microspheres, stir evenly, let stand to defoam, and obtain a gel system for blocking CO2 gas channeling in low-permeability reservoirs; In step (4), the pH of the low-viscosity pregel solution system is naturally maintained at 7.5 to 8.
8.
2. The gel system for plugging CO2 gas channeling in low-permeability reservoirs according to claim 1, characterized in that, The preparation method of the acrylamide-acrylic acid-glycidyl methacrylate terpolymer pre-crosslinked flexible microspheres includes the following steps: S1. Acrylamide, acrylic acid, glycidyl methacrylate, crosslinking agent, and emulsifier are added to deionized water and stirred until completely dissolved. The pH of the system is adjusted to 7.0-7.5, and emulsified for 30-40 minutes at 30-40℃ and 300-500r / min stirring speed to form a uniform emulsion. S2 is added as an initiator, and the reaction is carried out at a constant temperature of 40-50℃ for 2-3 hours to achieve in-situ polymerization and pre-crosslinking; After the S3 reaction is completed, the mixture is centrifuged, washed 2 to 3 times with deionized water, air-dried at room temperature, and pulverized to obtain acrylamide-acrylic acid-glycidyl methacrylate terpolymer pre-crosslinked flexible microspheres.
3. The gel system for plugging CO2 gas channeling in low-permeability reservoirs according to claim 2, characterized in that, The mass ratio of acrylamide, acrylic acid, and glycidyl methacrylate is (7~8):2:1; the amount of the initiator is 0.2~0.4% of the total mass of acrylamide, acrylic acid, and glycidyl methacrylate; the initiator includes ammonium persulfate and sodium bisulfite, with a mass ratio of (2.5~3.5):1; the crosslinking agent is N,N'-methylenebisacrylamide, and the amount of the crosslinking agent is 0.5~1% of the total mass of the monomers; the emulsifier is sodium dodecyl sulfate, and the amount of the emulsifier is 0.3~0.6% of the total mass of the monomers.
4. The gel system for plugging CO2 gas channeling in low-permeability reservoirs according to claim 1, characterized in that, The modified hydrophobic nano-silica was prepared by the following steps: S01 mixes nano-silica, ethanol, and water, stirs and ultrasonically disperses them to form a nano-silica dispersion; SO2 is added to a nano-silica dispersion as a silane coupling agent, and the mixture is refluxed at 55-65°C for 2-3 hours. Stearic acid is then added, and the reaction continues for another 1.5-2 hours. After the SO3 reaction is completed, the modified hydrophobic nano-silica is obtained by centrifugation, washing, drying, grinding and sieving.
5. The gel system for plugging CO2 gas channeling in low-permeability reservoirs according to claim 4, characterized in that, The mass ratio of nano-silica, ethanol, and water is (1~1.2):(8~8.5):(1.5~2); the silane coupling agent is KH-560, and the amount of the silane coupling agent is 4~6% of the mass of nano-silica; the amount of stearic acid is 3~4% of the mass of nano-silica.
6. The gel system for plugging CO2 gas channeling in low-permeability reservoirs according to claim 1, characterized in that, In step (1), the stirring speed is 300 ~ 500 r / min; in step (3), the stirring speed is 400 ~ 600 r / min; in step (5), the stirring speed is 200 ~ 300 r / min.
7. The application of the gel system for blocking CO2 gas channeling in low-permeability reservoirs according to any one of claims 1 to 6 in the blocking of gas channeling in low-permeability reservoirs.
Citation Information
Patent Citations
High-molecular pre-crosslinked gel particle blocking agent suitable for carbon dioxide flooding oil reservoir and preparation method of high-molecular pre-crosslinked gel particle blocking agent
CN121759180A
Horizontal well acidizing-based phase-state transformation acid
CN102634331A
Particulate profile control agent self-adaptive to pore throat size of stratum and preparation method for particulate profile control agent
CN110591679A